The 365 bullet guide :organizer your life creativity, one day at a time - Compton, Zennor; Mijotich, Marcia (London Macmillan, 2017)
The bullet system is an organizational method designed to increase efficiency and creativity. The bullet method provides a process for the user to organize their daily life, take note of past accomplishments, and plan the future. This 365 Bullet Guide contains an exercise for every day of the year, each taking 365 seconds or less to complete. The Bullet Guide user can incorporate the bullet method into their life as gradually or quickly as they like. Bulleting is both holistic and completely customizable to their own aesthetics and habits, allowing users to create their own journal from scratch and put into practice as many of the hundreds of ideas and techniques as they like such as habit trackers, sleep logs, handwriting exercises, and more. The Bullet Guidei is a guide to an organized life.
Get started -- Get creative I -- Work smarter, not harder -- Get creative II -- Look after your body -- Get creative III -- Look after your mind -- Get creative IV -- Organized fun -- Get creative V -- Life admin -- Get creative VI -- Masterclass.
"Originally published in the UK by Boxtree, an imprint of Pan Macmillan." -- Title page verso.
Keywords: Life skills; Self-help techniques; Behavior modification; Behavior modification; Life skills; Self-help techniques